Seasonality of Türkiye storm Frequency - Acar, Zahide (Bulletin of Geography. Physical Geography Series, 2023)
Continental windstorms are quite common in Türkiye as well as in the Mediterranean basin. These storms have high frequency during hot and cold periods and transition seasons. Türkiye is vulnerable to storms that are most effective in winter. When the distribution of the average number of stormy days during the year in Türkiye is analyzed by seasons, the season with the highest number of storms during the year is winter with a rate of 37%. The remaining seasons are spring (29%), fall (18%), and summer (16%). In the seasonal distribution of the storms that occur during the year, the winter season, which has the highest rate of occurrence, has an average of 4.9 days of storms. The spring and the autumn seasons are stormy 3.8 and 2.4 days, respectively. Storms have a high frequency during the cold season from October to May. Storms cause storm surges, floods, flash floods, and roof blow-off disasters in the coastal zone of Türkiye, causing loss of life and property in the cold seasons.